Phase separation of Ti-containing interpenetrating polymer networks depending on the kinetics of their formation - Ignatova, T.D.; Tsebrienko, T.V.; Vorontsova, L.O.; Alekseeva, T.T. (Reports of the National Academy of Sciences of Ukraine, 2017)
The process of phase separation and the morphology of organic-inorganic interpenetrating polymer networks (OI IPNs) based on the crosslinked polyurethane, poly(hydroxyethyl methacrylate) (PHEMA) and poly(ti tanium oxide) (—TiO2—)n obtained by the sol-gel method in the presence of poly(oxypropylene glycol) at various molar ratios of titanium isopropoxide (Ti(OPri)4) and water have been investigated. It is established that the phase separation in OI IPNs depends on the kinetics of formation of PHEMA-component, and it occurs through the mechanism of spinodal decomposition. It is shown that the process of phase separation can be controlled by va rying the ratios of components of IPNs, content of the inorganic component, and the molar ratio of Ti(OPri)4/H2O, and OI IPNs can be obtained with the different phase structures.